Learning in the forest: environmental perception of Brazilian teenagers - Profice, Christiana Cabicieri; Grenno, Fernando Enrique; Fandi, Ana Cláudia; Menezes, Stela Maria; Seminara, Cecília Inés; Cassano, Camila Righetto (Frontiers in Psychology, 2023)
The idea of separation between person and nature, accentuated by current production and consumption models, has generated unthinkable impacts, causing an unprecedented loss and degradation of the global environment. Occupying 13% of the Brazilian territory, the Atlantic Forest is the second-largest tropical rainforest on the American continent; however, it is one of the most threatened biomes in the world, with only 12% of the original cover. In this study, we consider that enabling young people to experience direct contact with nearby natural environments can positively influence their knowledge and feelings about the biodiversity that occurs there, contributing to its protection and conservation for current and future generations. In this study, we explore how teenagers (n=17) aged between 13 and 17 years old describe and perceive the nearby natural environment before and after an interpretive trail in Una, Bahia, Brazil. Participants were asked to draw the Atlantic Forest with colored pencils on white paper and, based on the drawing, they answered the following questions: “What is in your drawing? and “What is happening in your drawing?”, in addition to other information such as the title of the drawing, difficulty of the activity, and sociodemographic aspects. Content analysis was used to analyze the information collected. From the responses of the participants, categories related to knowledge, experiences, and types of relationships with the visited place emerged. The subsequent statistical analysis tested the frequency of each category before and after the visit, together with a qualitative analysis of the descriptions of their feelings and meanings attributed to the visit, highlighting the different elements and their relationships. The results showed that, after the trail, the participants manifested bonds of proximity with the visited environment and the beings protected there, evidencing expressive changes in their perceptions of the person-nature interaction, in the specific knowledge of the visited ecosystem, and in the different forms of relationship provided by the visitation itinerary.